Cover Image, Volume 235, Number 10, October 2020. Issue 10 (4th August 2020) - Li, Hui; Hao, Yu; Yang, Li‐Li; Wang, Xin‐Yang; Li, Xin‐Yu; Bhandari, Suwas; Han, Jun; Liu, Yong‐Jian; Gong, Yu‐Qiang; Scott, Aaron; Smith, Fang Gao; Jin, Sheng‐Wei
Abstract : The cover image is based on the Original Research Article MCTR1 alleviates lipopolysaccharide‐induced acute lung injury by protecting lung endothelial glycocalyx by Hui Li et al., https://doi.org/10.1002/jcp.29628 .